2022
DOI: 10.3390/antibiotics11030397
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Streptococcus agalactiae from Freshwater Fish and Pork in Hong Kong Wet Markets

Abstract: We report the antimicrobial resistance of 191 fish and 61 pork Group B Streptococcus (GBS) procured from Hong Kong wet markets. Two-hundred-and-fifty-two GBS strains were isolated from 992 freshwater fish and 361 pig offal during 2016–2019. The strains were isolated from homogenised samples and plated on selective media, followed by identification through MALDI-TOF-MS. Molecular characterisation, an antibiotic susceptibility test, and biofilm formation were performed on the strains. The isolation rates of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…GBS strains were subjected to serotyping by multiplex PCR as previously described [32][33][34]. Briefly, two to four bacterial colonies were incubated at 94 • C for five minutes in 200 µL lysis buffer (0.25% sodium dodecyl sulfate, 0.05 N NaOH) and centrifuged at 16,000 X g for five minutes before differentiating serotypes Ia, Ib, II-IX.…”
Section: Gbs Serotyping and Antibiotic Susceptibility Testmentioning
confidence: 99%
“…GBS strains were subjected to serotyping by multiplex PCR as previously described [32][33][34]. Briefly, two to four bacterial colonies were incubated at 94 • C for five minutes in 200 µL lysis buffer (0.25% sodium dodecyl sulfate, 0.05 N NaOH) and centrifuged at 16,000 X g for five minutes before differentiating serotypes Ia, Ib, II-IX.…”
Section: Gbs Serotyping and Antibiotic Susceptibility Testmentioning
confidence: 99%
“…Among the remaining 20 articles that employed intrinsic relationships between One Health and fish, eight were reviews rather than primary ones. Consequently, 12 final articles met all the criteria pre-established by this systematic review (Figure-1 and Table -3) [12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…Alhaji et al 2021 [12] Nigeria, West Africa Food control Scopus Brunton et al 2019 [13] Vietnam, Southeast Asia Science of the total environment Scopus Sapugahawatte et al 2022 [14] Hong Kong, China Antibiotics PubMed Das et al 2020 [15] Khorda, India JMIR research protocols Scopus Cerdeira et al 2020 [16] Belém, Brazil Genomics Scopus Minja et al 2021 [17] Tanzânia, East Africa Antibiotics Scopus Sapugahawatte et al 2020 [18] Hong Kong, China mSphere PubMed Pace et al 2020 [19] Naples [23] Uganda, East Africa Cogent Food and agriculture PubMed identify emergency hotshots of antibiotic-resistant bacteria attributed to human exposure. Thus, the results revealed that the growth stage of individuals is crucial for the emergence of highly resistant bacteria due to the exacerbated use of antimicrobials and the consequent exposure to contaminated water.…”
Section: Author Year Place Of Publication Journal Databasementioning
confidence: 99%
“…Macau and Hong Kong, both situated in the PRD Bay, are two densely populated regions (over 22,000 and 6700 hab./km 2 , respectively) that depend on the Hong Kong and Guangdong province fish industry (Chen et al 2008;AFCD 2021). For example, in Hong Kong, fresh food products are usually purchased from wet markets (Sapugahawatte et al 2022). It is also known that Hong Kong's demand and consumption of seafood is substantial, with a per capita average consumption of 66.5 kg, ranking second in Asia in 2017, showing the importance of these markets in the region (World Wildlife Fund n.d.).…”
Section: Highlightsmentioning
confidence: 99%